Analisis Potensi Longsor Pada Ruas Jalan Kawasan Wisata Mandeh-Sungai Nyalo Km 18 Kecamatan Koto XI Tarusan, Kabupaten Pesisir Selatan - Novia Afrizal; Yoszi Mingsi Anaperta; Riko Maiyudi (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. Based on observations that have been made on the Mandeh-Nyalo Tourism Area road section, it is found that the slopes which have many weak field structures in the form of burly, and the high intensity of the earthquake in West Sumatra greatly affect the stability of the slope conditions. From these problems, it is necessary to know the condition of rock mass on the study slope. Furthermore, it is necessary to analyze the slope stability. From the results of rock mass classification with the RMR system, the rocks are included in group II with good quality rock mass. Then, from the slope stability analysis using slide software, the slope stability value in the original condition was 1.95 and the saturation condition was 1.36. And based on the analysis of the slope stability value with the Hoek and Bray method, the slope stability value is 1.70.Keywords: Slope, landslides, rock mass, safety factors, strengthened